Comparative effectiveness of improvement in pain and physical function for baricitinib versus adalimumab, tocilizumab and tofacitinib monotherapies in rheumatoid arthritis patients who are naïve to treatment with biologic or conventional synthetic disease-modifying antirheumatic drugs: a matching-adjusted indirect comparison. Issue 1 (5th May 2020) - Fautrel, B; Zhu, B; Taylor, P C; van de Laar, M; Emery, P; De Leonardis, F; Kannowski, C L; Nicolay, C; Kadziola, Z; De La Torre, I; Fleischmann, R
Abstract : Objective: To compare improvement in pain and physical function for patients treated with baricitinib, adalimumab, tocilizumab and tofacitinib monotherapy from randomised, methotrexate (MTX)-controlled trials in conventional synthetic disease-modifying antirheumatic drugs (csDMARDs)/biologic (bDMARD)-naïve RA patients using matching-adjusted indirect comparisons (MAICs). Methods: Data were from Phase III trials on patients receiving monotherapy baricitinib, tocilizumab, adalimumab, tofacitinib or MTX. Pain was assessed using a visual analogue scale (0–100 mm) and physical function using the Health Assessment Questionnaire-Disability Index (HAQ-DI). An MAIC based on treatment-arm matching, an MAIC with study-level matching and Bucher's method without matching compared change in outcomes between therapies. Matching variables included age, gender, baseline disease activity and baseline value of outcome measure. Results: With all methods, greater improvements were observed in pain and HAQ-DI at 6 months for baricitinib compared with adalimumab and tocilizumab ( p <0.05). Differences in treatment effects (TEs) favouring baricitinib for pain VAS for treatment-arm matching, study-level matching and Bucher's method, respectively, were −12, −12 and −12 for baricitinib versus adalimumab and −7, −7 and −9 for baricitinib versus tocilizumab; the difference in TEs for HAQ-DI was −0.28, −0.28 and −0.30 for adalimumab and −0.23, −0.23 and −0.26 for tocilizumab. For baricitinib versus tofacitinib, no statistically significant differences for pain improvement were observed except with one of the three methods (Bucher method) and none for HAQ-DI. Conclusions: Results suggest greater pain reduction and improved physical function for baricitinib monotherapy compared with tocilizumab and adalimumab monotherapy. No statistically significant differences in pain reduction and improved physical function were observed between baricitinib and tofacitinib with the MAIC analyses.